Protection of Erythrocytes and Microvascular Endothelial Cells against Oxidative Damage by Fragaria vesca L. and Rubus idaeus L. Leaves Extracts-The Mechanism of Action - Cyboran-Mikołajczyk, Sylwia; Męczarska, Katarzyna; Solarska-Ściuk, Katarzyna; Ratajczak-Wielgomas, Katarzyna; Oszmiański, Jan; Jencova, Vera; Bonarska-Kujawa, Dorota (Molecules, 2022)
The aim of this work is to determine the biological activity of ellagitannins rich extracts from leaves of raspberry (Rubus idaeus L.) and wild strawberry (Fragaria vesca L.) in relation to cells and cell membranes. Detailed qualitative and quantitative analysis of phenolic compounds of the extract was made using chromatographic methods. Cytotoxic and antioxidant activities of tested extracts in relation to erythrocytes and human vascular endothelial cells (HMEC-1) were determined by using fluorimetric and spectrophotometric methods. In order to establish the influence of the extracts on the physical properties of the membrane, such as osmotic resistance and erythrocytes shapes, mobility and/or hydration of polar heads and fluidity of hydrocarbon chains of membrane lipids, microscopic and spectroscopic methods were used. The results showed that the extracts are non-toxic for erythrocytes and HMEC-1 cells (up to concentration of 50 μg/mL), but they effectively protect cells and their membranes against oxidative damage. The increase in osmotic resistance of erythrocytes, formation of echinocytes and changes only in the polar part of the membrane caused by the extracts demonstrate their location mainly in the hydrophilic part of the membrane. The results indicate that tested extracts have high biological activities and may be potentially used in delaying the ageing process of organisms and prevention of many diseases, especially those associated with oxidative stress.
Keywords: Antioxidants; jahodník; oxidační stres; rostlinné extrakty; erytrocyty; Oxidative Stress; lidé; Hydrolyzable Tannins; Endothelial Cells; Membrane Lipids; Rubus; hydrolyzovatelné taniny; Erythrocytes; antioxidancia; endoteliální buňky; Plant Extracts; Fragaria; membránové lipidy; Humans